2010
DOI: 10.1242/jeb.040139
|View full text |Cite
|
Sign up to set email alerts
|

Mating-induced transient inhibition of responses to sex pheromone in a male moth is not mediated by octopamine or serotonin

Abstract: SUMMARYIn the male moth, Agrotis ipsilon, mating induces a transient inhibition of behavioural and central nervous responses to sex pheromone. Newly mated males are not attracted to sex pheromone, and the sensitivity of their antennal lobe (AL) neurons is lower than in virgin males. This rapid transient olfactory inhibition prevents them from re-mating unsuccessfully until they have refilled their sex glands. We hypothesized that this olfactory 'switch off' might be controlled by neuromodulators such as biogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…Interestingly, by detailed analysis of MGC neuron responses to sex pheromone, we found a clear pheromone response threshold of 1ng, indicating that at this level the pheromone starts to elicit a response in the brain of newly mated males. We have recently shown that mating indeed induced drastic changes in the responses of AL neurons to the pheromone in mated males; together with changes in spike frequency, the latency, and durations of excitatory and inhibitory phases were also changed as compared with virgin males (Barrozo et al, 2010). This could explain the observed lack of response of newly mated males in the wind tunnel: below a specific threshold, males do not detect the pheromone and therefore do not respond; above this threshold, males do detect the pheromone, which has become inhibitory.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Interestingly, by detailed analysis of MGC neuron responses to sex pheromone, we found a clear pheromone response threshold of 1ng, indicating that at this level the pheromone starts to elicit a response in the brain of newly mated males. We have recently shown that mating indeed induced drastic changes in the responses of AL neurons to the pheromone in mated males; together with changes in spike frequency, the latency, and durations of excitatory and inhibitory phases were also changed as compared with virgin males (Barrozo et al, 2010). This could explain the observed lack of response of newly mated males in the wind tunnel: below a specific threshold, males do not detect the pheromone and therefore do not respond; above this threshold, males do detect the pheromone, which has become inhibitory.…”
Section: Discussionmentioning
confidence: 98%
“…Although biogenic amines have been shown to be involved in the modulation of pheromone sensitivity in animals including insects, octopamine and serotonin are probably not involved in the transient post-mating olfactory switch-off in A. ipsilon males (Barrozo et al, 2010). As an analogy to what is known for the lack of receptivity and pheromonostasis following mating in females, we will test the hypothesis that there could be either an inhibitory factor present or a stimulatory factor lacking in the sex accessory glands or in some part of the brain in newly mated A. ipsilon males.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations